Various Components and the present Scenario of Skill Development (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Literacy enhances people's knowledge and abilities. Literacy as a fundamental human right is becoming more widely recognized across the globe. Because of this, learning never ends. Having skill makes any task easier to do. Practical education builds on previously gained information, and the two go hand in hand. Formal and informal channels of information dissemination have both been used by educational institutions. Making a student financially independent is one of the primary goals of formal education. College degrees are a boon to society in many ways, both financially and otherwise. Higher education students who participate in skill development programs get insight into themselves while also gaining practical knowledge, increasing their productivity, and realizing their full potential. Undergraduate students who were previously aimlessly pursuing higher education now have an alternate schooling option because to the social logic of these programs. But for skill development programs to be accessible, equitable, informative, and engaging for undergraduates—who "...have miles to go before they sleep"—and to be meaningful and effective in light of the changing global scenario, careful planning is essential.